The new development of centrifugal cruncher system for composite material application / Muhammad Iqbal Ahmad … [et al.] - Ahmad, Muhammad Iqbal; Abdullah, Azwan; Abdul Wahab, Abdul Rahim; Ja'afar, Hanafi; Lamree, Siti Rodhiah; Ramlan, Noor Wahidah; Othman, Rozaini (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
A Centrifugal Cruncher is primarily used for pulverizes the material after it crushed. It includes the ferrous metal and non-ferrous (composite) metal, glass ceramics or etc. Rotating materials that provide a violations impact in the rotating cylinder which produces centrifugal force to a certain height after the fall and it have severe impact and abrasive. This research product is known as "The New Development of Centrifugal Cruncher System for Composite Material". The design of our product consists of 240 W AC motor, several aluminium shaft, and some rectifier has been used to control the speed of rotation. From research conducted, relationship between density, hardness, and composition of grinding media also the material being ground. Then, in this product we have various type of rotating cylinder and we differed it by the diameter and material used. This technique has proven useful for generating ultra-fine amorphous materials for achieving crystalline structure. Centrifugal Cruncher can satisfy different requirement, and have good features such as low consumption, high capacity per hour, improved rotation per minute, no pollution to the environment around, and it easy to be repaired. It is also having space because of its size with light weight and easy to move everywhere.